Crocin Improves Endothelial Mitochondrial Dysfunction via GPx1/ROS/KCa3.1 Signal Axis in Diabetes - Li, Xuemei; Liu, Yang; Cao, Anqiang; Li, Chao; Wang, Luodan; Wu, Qing; Li, Xinlei; Lv, Xiaohong; Zhu, Jiwei; Chun, Hua; Laba, Ciren; Du, Xingchi; et al. (Frontiers in Cell and Developmental Biology, 2021)
Mitochondrial dysfunction contributes to excessive reactive oxygen species (ROS) generation, which is a dramatic cause to promote endothelial dysfunction in diabetes. It was previously demonstrated that crocin protected endothelium based on its diverse medicinal properties, but its effect on mitochondrion and the potential mechanism are not fully understood. In this study, mitochondrial function was analyzed during the process of excessive ROS generation in high glucose (HG)-cultured human umbilical vein endothelial cells (HUVECs). The role played by KCa3.1 was further investigated by the inhibition and/or gene silence of KCa3.1 in this process. In addition, NADPH oxidases 2 (NOX2) , superoxide dismutase 1 (SOD1) and glutathione peroxidase 1 (GPx1) were also detected in this study. Our data showed that crocin improved mitochondrial dysfunction and maintained normal mitochondrial morphology by enhancing the mitochondrial membrane potential (MMP), mitochondrial mass, and mitochondrial fusion. Furthermore, KCa3.1 was confirmed to be located in the mitochondrion and the blockade and/or silencing of KCa3.1 improved mitochondrial dysfunction and reduced excessive ROS generation, but not affected NOX2 and/or SOD1 system. Intriguingly, it was confirmed that KCa3.1 expression was elevated by ROS overproduction in endothelium under HG and/or diabetes conditions, while crocin significantly suppressed this elevation by promoting GPx1 and subsequently eliminating ROS generation. In addition, crocin enhanced CD31, thrombomodulin (TM) and p- /t-eNOS expressions as well as NO generation and decreased vascular tone. Hence, crocin improved mitochondrial dysfunction through inhibiting ROS-induced KCa3.1 overexpression in endothelium, which in turn reduced more ROS generation and final endothelial dysfunction in diabetes.